Pharma Industry –The Shining Star for India - Tikkha , Manas (International Journal of Scientific Research and Management (IJSRM), 2023)
India is now accepted as global manufacturing & research hub in pharmaceutical sector. It is growing at rapid pace in worldwide In pharmaceutical sector India is ranked 14th in terms of value & 3rd in terms of production with also a strong network of 3000 drug companies & 10500 manufacturing unit. Excessive availability of skilled workforce & raw material has given the sector an enormous advantage. India is the biggest supplier for generic medicines overseas with fulfilling 60% of vaccine demand globally. It is also fulfilling 20% of worldwide demand supply by volume also. It contributes about 1.72% of country’s GDP.